Reliability and risk assessment - Andrews, J. D. (John D.) 1957- (Longman Scientific & Technical, 1993)
Accidents at process plants such as Windscale, Piper Alpha and Chernobyl have created worldwide concern over the risks involved in operating hazardous plant. Thorough procedures for the assessment and reliability testing of safety systems are now in great demand. Reliability and Risk Assessment provides a full theoretical background to the techniques used in this field of engineering and discusses how these methods are applied in practice. The authors show how these methods can be used to improve not only the safety records, but also the efficiency, productivity and profitability, of processing plants. Reliability and Risk Assessment is intended primarily as a reference for professional engineers, but will also prove invaluable for postgraduate students involved in reliability and risk assessment research.